Acceleration feedforward control in active magnetic bearing system subject to base motion by filtered-X LMS algorithm - Min Sig Kang, Min Sig Kang; Woo Hyun Yoon, Woo Hyun Yoon (IEEE transactions on control systems technology, 2006)
This brief addresses the application of an active magnetic bearing (AMB) system to levitate the elevation axis of an electro-optical sight mounted on a moving vehicle. In this type of system, it is desirable to retain the elevation axis in an air-gap between magnetic bearing stators while the vehicle is moving. An optimal acceleration feedforward compensator design technique is proposed to attenuate disturbance responses in an AMB system that is subject to base motion. In consideration of the sensitivity of the disturbance compensation performance to the model accuracy, an experimental feedforward compensator is developed from an adaptive estimation by means of the filtered-x least mean square (FXLMS) algorithm. The compensation control is applied to a single degree of freedom (DOF) AMB system subject to base motion. The feasibility of the proposed technique is illustrated, and the results of an experimental demonstration are shown.